PERANCANGAN APLIKASI PEMESANAN TIKET ONLINE BERBASIS WEB MENGGUNAKAN METODE AGILE (STUDI KASUS : TIRTA SUMBER JAYA CIPANGALUN) - Fauzan Mutaqin, Restu; Dwicahya Supriatman, Rian; Mulyana, Dadan (Fakultas Teknik Jurusan Sistem Informasi Universitas Galuh, 2025)
This research aims to make it easier for customers to order tickets at Tirta Sumber Jaya and for admins to manage ticket ordering data and staff who check e-ticket QR. Previously, Tirta Sumber Jaya still used manual methods for ticket sales services. This makes services ineffective and inefficient, such as recording ticket sales and customer queues taking a long time. In solving this problem the author used the Agile Method in designing the online ticket booking application. The results of research conducted at Tirta Sumber Jaya, the developed application, can make it easier for admins to process ticket orders at Tirta Sumber Jaya and make transactions easier, faster, and more efficient